RESEARCH OF THE MOBILE TOWER CRANE TOWER DOWN FOUR-BAR LINKAGE - SHANGGUAN JianLin; LIU DePing (Jixie qiangdu)
To solve the problem of transition of the tower crane with high center of gravity,through sex difference,fixed transportation for the tower body and its attached parts being put down may be regarded as a fast and efficient method. Four-bar linkage was adopted to put down the towerbody,its working principle is introduced,then the force analysis of its components is carried,finally,its simulation and optimization is carried out through using MATLAB. The feasibility and practicability of the method are verified by numerical examples and engineering practice.